Estudo comparativo do efeito da Echinácea purpúrea e sorafenibe em células de adenocarcinoma renal humano em cultura - Tassetano, Renata Cristina Tornelli [UNIFESP] (2010)
Introduction: The renal cell carcinoma (CR) is relatively rare compared to other cancers. One of the most potent tumor mitogen, vascular endothelial growth factor, VEGF is regulated by numerous pathways, especially Ras and Akt, which are targets of many therapeutic agents, among them sorafenib. These signaling pathways play an important role in the development and maintenance of the multidrug resistance (MDR). Echinacea purpurea is used as an alternative treatment for some cancers, and promising for the treatment of CR. Aim: Analyze the effect of Ech purpurea (Ech) on the cellular viability, apoptosis, Ras and Akt signaling pathway as well as tumor angiogenesis throughout VGEF and potential proteins alteration in the cellular resistance to drugs. Methods: Herbal echinacea were added to cell culture Caki-1 for subsequent analysis of cell viability (Crystal Violet), apoptosis (flow cytometry), release of the enzyme lactate dehydrogenase - LDH (Bio 200), protein expression of VEGF, Ras and Akt (Western blot ) and gene expression MDR, MRP, LRP (RT-PCR). The experiments were performed after 24, 48 and 72 hours of treatment. The results were analyzed by One Way ANOVA, p <0.001 vs CT (X ± SE vs CT). Results: Group treated with Ech demonstrated decrease in cell viability dose and time dependent compared to the control (IC50, 150mg/mL) from 0 to 300ug/mL (p<0.001). We observed a statistically significant increase of apoptotic cells for group 72 hours comparing with control group: 4.7±0.4 vs. 7.6±0.7 (p<0.001), respectively. Also, a decrease in protein expression (p<0.05) of the Akt (0.301±0.02 vs. 0.193±0.009) and VEGF (0.729±0.01 vs. 0.439±0.01) in 48 hours, as well as Ras in 24 hours (0.484±0.05 vs. 0.289±0.02) were obtained. By analyzing the genic expression of the proteins resistance to multiple drugs, Ech caused a substantial decrease of 100% for MDR and MRP with 25% decreases in LRP, suggesting an important effect in blunt the resistance protein to drugs. Conclusion: To our knowledge, the Ech has anti-oncogenic properties since it showed activity on the viability and apoptosis. Likewise, Ech has its role on the signaling pathways Akt and Ras, which are important mediators of cell cycle progression and apoptosis. These blunted pathways demonstrated an important role on VEGF inhibition, as well as in the regulation of multidrug resistance.